A Modification of the Anoplasty Technique during a Posterior Sagittal Anorectoplasty and Anorectal Vaginal Urethroplasty Closure: The Para-U-Stitch to Prevent Wound Dehiscence - Knaus, Maria E.; Westgarth-Taylor, Christopher; Gasior, Alessandra C.; Halaweish, Ihab; Thomas, Jessica L.; Srinivas, Shruthi; Levitt, Marc A.; Wood, Richard J. (European Journal of Pediatric Surgery, 2023)
Objective Wound dehiscence after posterior sagittal anorectoplasty (PSARP) or anorectal vaginal urethroplasty (PSARVUP) for anorectal malformation (ARM) is a morbid complication. We present a novel anoplasty technique employing para-U-stitches along the anterior and posterior portions of the anoplasty, which helps buttress the midline U-stitch and evert the rectal mucosa. We hypothesized that, in addition to standardized pre- and postoperative protocols, this technique would lower rates of wound dehiscence.Materials and Methods A retrospective review of patievnts who underwent primary PSARP or PSARVUP with the para-U-stitch technique from 2015 to 2021 was performed. Wound dehiscence was defined as wound disruption requiring operative intervention within 30 days of the index operation. Superficial wound separations were excluded. Descriptive statistics were calculated. The final cohort included 232 patients.Results Rectoperineal fistula (28.9%) was the most common ARM subtype. PSARP was performed in 75% and PSARVUP in 25%. The majority were reconstructed with a stoma in place (63.4%). Wound dehiscence requiring operative intervention occurred in four patients, for an overall dehiscence rate of 1.7%. The dehiscence rate was lower in PSARPs compared with PSARVUPs (0.6 vs. 5.2%) and lower for reconstruction without a stoma compared with a stoma (1.2 vs. 2.0%). There were additional six patients (2.6%) with superficial wound infections managed conservatively.Conclusion We present the para-U-stitch anoplasty technique, which is an adjunct to the standard anoplasty during PSARP and PSARVUP. In conjunction with standardized pre- and postoperative protocols, this technique can help decrease rates of wound dehiscence in this patient population.
Keywords: anorectal malformation; dehiscence; cloaca; PSARP; PSARVUP